PRELIMINARY OBSERVATION ON THE LUNAR AND TIDAL INFLUENCES ON THE CATCHES OF SEER BY GILL NETS - MATHAI, T JOSEPH; ABRAHAM, RAJAN; SULOCHANAN, P; SADANANDAN, K A (Fishery Technology, 2025)
The paper deals with the lunar and tidal influences on thecatches of seer by gill nets. The landings during fuH-moon and new=moon nights, during low and high tides and during differentquarters of the lunar month for three fishing seasons are discussed.